Method for preparing nitrate ammonia fertilizer by utilizing electroplating wastewater containing nitric acid

The nitrate in the electroplating wastewater is reduced to ammonia through electrocatalytic technology, and nitrate fertilizer is prepared in combination with ammonium nitrate solution and other steps, which solves the problem of low resource utilization rate of electroplating wastewater and achieves efficient and environmentally friendly nitrogen resource utilization.

CN119591436APending Publication Date: 2025-03-11SOUTH CHINA INST OF ENVIRONMENTAL SCI MEP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411704555.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the resource utilization rate of electroplating wastewater is relatively low, and it is difficult to effectively utilize the heavy metal and nitrogen resources therein.

Method used

The nitrate ions in the nitric acid-containing electroplating wastewater are reduced to ammonia by electrocatalytic technology, and the granular nitrate ammonia fertilizer is prepared by mixing with the ammonium nitrate solution, adding phosphorus and potassium, and evaporation and concentration.

Benefits of technology

The resource utilization of heavy metals and ammonia in nitric acid wastewater has been realized, the resource utilization rate of wastewater has been improved, production costs have been reduced, and the fertilizer efficiency and environmental protection of nitrate ammonia fertilizer has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591436A_ABST
    Figure CN119591436A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of nitrate ammonia fertilizers, in particular to a method for preparing a nitrate ammonia fertilizer from nitric acid-containing electroplating wastewater. Comprising the following steps: S1, electrocatalysis of nitric acid-containing electroplating wastewater; S2, preparation of a nitrate ammonia fertilizer; according to the method, ammonia and heavy metal in the electrolyte are effectively precipitated and separated out by utilizing the electrocatalysis effect of the nitric acid-containing wastewater, and the nitrate ammonia fertilizer is prepared from the obtained ammonia, the treated ammonium nitrate solution and trace elements, so that resource utilization of the heavy metal and ammonia in the nitric acid wastewater is realized, and cost reduction and efficiency improvement are facilitated; the problem that in the prior art, the resource utilization rate of wastewater is low is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nitrate ammonia fertilizer preparation, and in particular to a method for preparing nitrate ammonia fertilizer by utilizing electroplating wastewater containing nitric acid. Background Art

[0002] Wastewater is generated in each production link of the electroplating process. Not only is the amount of wastewater large, but also there are many types of wastewater, including pre-plating degreasing wastewater, organic matter removal wastewater, plated parts rinsing wastewater, tank washing wastewater, waste plating liquid, and laboratory water wastewater. Pickling is one of the indispensable processes in the electroplating process. All materials of different substrates must be pickled before entering the electroplating solution, and the types and concentrations of the treatment liquids after pickling are also different. Nitric acid pickling is one of the methods for removing oxides on the surface of workpieces by pickling process. In addition, copper-containing nitric acid etching liquid is also produced in the electroplating process. At present, the main treatment methods for heavy metal wastewater are mainly chemical methods (neutralization precipitation and sulfide precipitation) and oxidation methods, which usually produce a large amount of sludge and require additional treatment. The treatment methods for nitrate ions in wastewater are mainly chemical denitrification and biological denitrification. The resource utilization of heavy metals and nitrogen in nitric acid wastewater is conducive to cost reduction and efficiency improvement.

[0003] Electrocatalytic reduction is an alternative method for treating wastewater by combining electrochemical and catalytic technologies. By applying an electric current to the cathode, nitrates undergo an electrochemical reduction reaction, partially converting them into ammonia (NH3). Since the extraction of ammonia from the solution requires a lot of energy consumption and high technical equipment requirements, we propose a method for preparing nitrate-ammonia water-soluble fertilizer by increasing the conversion of nitrate. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing nitrate ammonia fertilizer by utilizing electroplating wastewater containing nitric acid.

[0005] The technical solution of the present invention is: a method for preparing nitrate ammonia fertilizer by utilizing electroplating wastewater containing nitric acid, comprising the following steps:

[0006] S1. Electrocatalytic nitric acid-containing electroplating wastewater

[0007] The nitric acid-containing electroplating wastewater is used as an electrolyte and passed through the cathode reduction zone into an electrochemical reactor, a catalyst is added according to a ratio of 1L of nitric acid-containing electroplating wastewater to catalyst of 0.2-0.5g, and electricity is applied, and the current is adjusted to reduce nitrate ions in the electrolyte to obtain ammonia and collect it, and as the pH near the cathode increases, heavy metal precipitation is initially removed, and the pH is further adjusted to 1-7 to remove the heavy metal precipitation for a second time, and the heavy metal precipitation is filtered to obtain an ammonium nitrate solution; wherein the heavy metals in the nitric acid-containing electroplating wastewater are mainly copper, tin, nickel, and zinc;

[0008] S2. Preparation of nitrate ammonia fertilizer

[0009] The extracted ammonia is mixed with an ammonium nitrate solution in a mass ratio of 1:1-2 to obtain a mixture, and then 8-10wt% of phosphorus and 5-7wt% of potassium are added to the mixture and mixed, and evaporated and concentrated under the conditions of 0.3-0.5MPa and 45-60°C to obtain liquid nitrogen fertilizer, and then the liquid ammonia fertilizer is dried and granulated to obtain granular nitrate ammonia fertilizer with a particle size of 0.5-2mm.

[0010] The advantages of nitrate ammonia fertilizer lie in its rapid effectiveness, high fertilizer efficiency, wide range of application, high safety, good environmental protection and high cost-effectiveness.

[0011] Furthermore, the current density is 20-200 mA / cm 2 ;

[0012] Note: The electrocatalytic nitrate reduction under the above current density can increase the pH near the cathode, forming a concentration gradient, and precipitate the metal ions at a certain distance from the electrode, thereby effectively avoiding the direct precipitation of metal elements at the cathode.

[0013] Furthermore, the catalyst is selected from any one of metallic copper, carbon nanotubes, copper-palladium alloy, and metal molecular complex;

[0014] Description: The above-mentioned catalyst can be used to convert nitrate into ammonia with high selectivity, high current efficiency, high ammonia selectivity and low by-product nitrite.

[0015] Furthermore, the catalyst is modified with a quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot material having an average particle size of 5 to 50 nm; the preparation method of the quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot material is:

[0016] 1) Under magnetic stirring, 7 mol / mL cadmium nitrate solution, chitosan and the first additive are mixed in the ratio of 4-10 mL: 5-10 mmol: 1-2 mmol, and then pH regulator is added to adjust the pH to 7-9 to obtain a cadmium precursor solution containing chitosan; nitric acid-containing wastewater, heavy metal precipitate and sulfur source are mixed and stirred in the ratio of 5-15 mL: 3-5 mmol: 5-10 mmol until all dissolved, and deionized water is added to dilute to S 2- The concentration of is 0.15-0.25 mmol / L to obtain a sulfur precursor solution; the pH regulator is ammonia water;

[0017] 2) then dripping the sulfur precursor solution into the cadmium precursor solution containing chitosan at a rate of 3 to 10 mL / s, adding the second additive at the same time, heating and reflux at a constant temperature of 85 to 100° C. for 3 to 5 hours, and collecting the first quantum dot solution;

[0018] 3) centrifuging the first quantum dot solution at a speed of 2500-3000 r / min, removing the supernatant, dispersing the resulting precipitate in n-octadecene at a concentration ratio of 5-10 mg / mL, repeating the operation 2-4 times, and finally dissolving the precipitate in deionized water to obtain a second quantum dot solution;

[0019] 4) nitrogen is passed through the second quantum dot solution at a temperature of 22 to 30° C. for 15 to 45 minutes, and a quaternary ammonium salt solution and a nanosilver solution are sequentially injected with a syringe under magnetic stirring, with a dripping speed of 1 to 5 mL / min and a dripping time of 15 to 20 minutes, and then heated under reflux at 85 to 100° C. for 3 to 10 hours to obtain a reaction solution;

[0020] 5) aging the reaction solution in a water bath at a temperature of 30 to 180° C. for 0.5 to 2 h, crushing and granulating to obtain a quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dot material;

[0021] The sulfur source is n-dodecyl mercaptan or sulfur powder; the quaternary ammonium salt solution is composed of behenyl quaternary ammonium salt and deionized water in a weight ratio of 1:95-105; the nanosilver solution is composed of nanosilver and deionized water in a weight ratio of 1:20-25;

[0022] Description: Chitosan, as a natural polymer material, has good biocompatibility and degradability, better environmental protection, reduces pollution to the environment, and can form stable complexes with metal nanoparticles. This complex can improve the catalytic activity of copper nanoparticles, allowing them to participate in the reaction more effectively during the electrolysis process, thereby improving the electrolysis efficiency; quaternary ammonium salt-modified catalysts can attract nitrate ions through electrostatic action and inhibit the occurrence of other side reactions, making nitrate more inclined to be converted into ammonia, thereby increasing the ammonia conversion rate and improving the ammonia recovery capacity, thereby improving the preparation efficiency of ammonia fertilizer.

[0023] Sulfur can interact with copper surface atoms to form copper-sulfur bonds, change the electron cloud distribution of surface atoms, and thus produce more active sites. These active sites can adsorb more electrolytic reaction substrates and promote the electrolytic reaction. During the electrolysis process, metallic copper is easily oxidized, and the modified layer of the sulfur precursor can play a certain protective role, preventing oxygen from contacting the copper surface, maintaining the activity of the copper surface, and thus facilitating the continuous and efficient promotion of the electrolysis process. When the sulfur precursor modifies the catalyst, the metal ions in the heavy metal precipitate will also be doped into the structure of the catalyst, and the sulfur element will also interact with the surface of the carbon nanotubes. This modification can adjust the electronic structure of the carbon nanotubes and improve their conductivity, thereby increasing the rate of the electrolytic reaction. In addition, the modification of the sulfur precursor by heavy metal precipitation can also cause the metal center or ligand in the metal molecular complex to interact with the sulfur source, enhance the stability of the complex, thereby maintaining its catalytic activity and reducing the activity reduction caused by structural damage.

[0024] Furthermore, the first additive is a complexing agent, and the second additive is a surfactant; the complexing agent is ethylenediaminetetraacetic acid or polyacrylic acid, and the surfactant is sodium dodecyl sulfate or sodium stearate;

[0025] Description: Both ethylenediaminetetraacetic acid and polyacrylic acid can form complexes with cadmium ions. In the process of preparing cadmium precursor solution, this complexation helps to control the release rate and existence form of cadmium ions. It can prevent cadmium ions from precipitating prematurely or reacting with other impurities unnecessarily, so that cadmium ions can participate in subsequent reactions more evenly, and help to build a more stable quantum dot structure. When the quantum dot material is used in ammonia conversion reactions related to catalysts, the stable quantum dot structure is conducive to improving the efficiency of the reaction, thereby indirectly improving the ammonia recovery rate; in the process of dripping sulfur precursor solution into cadmium precursor solution, sodium dodecyl sulfate or sodium stearate as a surfactant can reduce the surface tension of the solution, which helps the two precursor solutions to mix better and make the reaction more complete; in the subsequent reaction, sodium dodecyl sulfate or sodium stearate can be adsorbed on the surface of quantum dots to prevent quantum dots from agglomerating and improve the dispersibility of quantum dots, which helps quantum dots to contact the catalyst surface more effectively and improve the activity of the catalyst, thereby improving the ammonia recovery rate in the process of converting nitrate ions into ammonia.

[0026] Furthermore, the catalyst modification method is as follows: firstly, the catalyst is ultrasonically dispersed in acetone with a concentration of 95-97% at a volume ratio of 20-40% to obtain a catalyst solution, and then the catalyst solution is ultrasonically mixed with quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots at a weight ratio of 3-10:5-8 to obtain a modified catalyst; the parameters of the ultrasonic dispersion and ultrasonic mixing are: ultrasonic power of 100-200W, ultrasonic time of 25-40min, and ultrasonic temperature of 35-50°C;

[0027] Note: Acetone can better disperse the catalyst particles and reduce agglomeration. In the subsequent ultrasonic mixing with quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots, the well-dispersed catalyst can contact the quantum dots more evenly. This uniform contact is conducive to the effective modification of quantum dots on the catalyst surface, so that in the process of converting nitrate to ammonia, the quantum dots can better play the role of improving the catalyst activity, selectivity, etc., and improve the ammonia recovery effect.

[0028] Furthermore, the granular nitrate ammonia fertilizer is subjected to an enhanced treatment, and the method of the enhanced treatment is:

[0029] 1) a strongly acidic cation exchange resin containing carboxyl groups, a strongly basic anion exchange resin containing γ-polyglutamic acid and polylactic acid are mixed in a solvent in a ratio of 1:1:0.5-0.8:2-4, and ultrasonically dispersed at an ultrasonic intensity of 55-75W and an ultrasonic temperature of 25-30°C to obtain a mixed solution A;

[0030] 2) The mixed solution A is uniformly attached to the surface of the granular nitrate ammonium fertilizer to obtain a reinforced film, and then dried and solidified at 40-60°C;

[0031] 3) Repeat step 2) 3 to 5 times to obtain granular nitrate ammonium fertilizer with a strengthening coating attached to the surface;

[0032] Description: The polymer used is polylactic acid, which has the characteristics of biodegradability and is environmentally friendly. The above-mentioned enhanced treatment can limit the entry of water into the fertilizer to dissolve nitrate ammonia when the soil humidity is low, thereby enhancing the ability to resist humid environments. When the ion concentration near the plant roots changes, nitrate ammonia can be released as needed to achieve the role of fertilizer.

[0033] Furthermore, in step 2), the thickness of the strengthening film is 10 to 50 nm, and the strengthening film is attached by vacuum magnetron sputtering or ion plating;

[0034] Note: The above attachment method can effectively ensure the effect of the mixed solution A on the surface of the granular nitrate ammonia fertilizer, thereby improving the performance of the fertilizer.

[0035] Furthermore, the content of carboxyl groups in the strongly acidic cation exchange resin containing carboxyl groups is 20-30 wt %, the content of γ-polyglutamic acid in the strongly basic anion exchange resin containing γ-polyglutamic acid is 15-18 wt %, and the solvent is dimethyl sulfoxide or water;

[0036] Description: Dimethyl sulfoxide has good solubility for carboxyl groups in strongly acidic cation exchange resins, γ-polyglutamic acid in strongly basic anion exchange resins, and polylactic acid; under ultrasonic conditions, the high polarity of dimethyl sulfoxide helps to reduce the viscosity of the system, allowing the ion exchange resin to be better dispersed, and it also has good solubility for polylactic acid, a polymer with a certain polarity; water is a polar solvent and has a certain affinity for strongly acidic cation exchange resins containing carboxyl groups and strongly basic anion exchange resins containing γ-polyglutamic acid. Although polylactic acid has poor solubility in water, under ultrasonic conditions, due to the dispersing effect of strongly acidic cation exchange resins and strongly basic anion exchange resins in water, polylactic acid can be evenly dispersed in the system in the form of small particles. At the same time, water has the advantages of low cost and environmental friendliness.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention utilizes the electrocatalytic effect of nitric acid-containing wastewater to effectively precipitate ammonia and heavy metals in the electrolyte, and prepares nitrate ammonia fertilizer by combining the obtained ammonia with the treated ammonium nitrate solution, thereby realizing the resource utilization of heavy metals and ammonia in the nitric acid wastewater, which is beneficial to reducing costs and increasing efficiency, and solving the problem of low resource utilization rate of wastewater in the prior art.

[0039] (2) The present invention achieves the promotion effect in the electrocatalytic process by modifying the catalyst surface with chitosan-CdS quantum dot materials modified with quaternary ammonium salt / nanosilver. Components such as nanosilver and CdS may form a good electron conduction channel inside the quantum dot. When in contact with the catalyst, this electron conduction property can promote the electron transfer of the catalyst in the process of converting nitrate to ammonia, accelerate the reaction process, and improve the ammonia conversion rate. Chitosan has good biocompatibility and degradability, and can form a stable complex with metal nanoparticles. This complex can improve the catalytic activity of the metal nanoparticles, allowing them to participate in the reaction more effectively during the electrolysis process. The catalyst modified with quaternary ammonium salt can attract nitrate ions by electrostatic action and other means, while inhibiting the occurrence of other side reactions, thereby effectively improving the electrolysis ability of the catalyst and reducing the generation of by-products.

[0040] (3) The present invention can restrict the entry of water into the fertilizer to dissolve nitrate ammonia when the soil moisture is low by strengthening the treatment of granular nitrate ammonia fertilizer, thereby enhancing the ability to resist humid environment; and when the ion concentration near the plant root system changes, nitrate ammonia can be released as needed to achieve the function of fertilizer, effectively enhancing the effect of nitrate ammonia fertilizer. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a comparison chart of ammonia conversion rates of Examples 1 to 8 of the present invention and Control Group 1;

[0042] Figure 2 It is a comparison chart of ammonia conversion rates of Example 1, Examples 9 to 23 and Control Groups 2 to 5 of the present invention;

[0043] Figure 3 It is a comparison chart of the conversion rates of ammonia of Example 9, Examples 24 to 30 of the present invention and the blank group and the control group 6 to the control group 7;

[0044] Figure 4 It is a comparison chart of the yield increase rate after the nitrate ammonia fertilizer of Example 9, Example 24 to Example 30 of the present invention and the blank group and the control group 6 to the control group 7 acted on spring wheat. DETAILED DESCRIPTION

[0045] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0046] Embodiment 1: A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid, comprising the following steps:

[0047] S1. Electrocatalytic nitric acid-containing electroplating wastewater

[0048] The nitric acid-containing electroplating wastewater is used as an electrolyte and passed through the cathode reduction zone into the electrochemical reactor. The catalyst is added according to the ratio of nitric acid-containing electroplating wastewater to catalyst of 1L:0.3g and electricity is applied. The current is regulated until the nitrate ions in the electrolyte are reduced to obtain ammonia and collected. As the pH near the cathode increases, the heavy metal precipitate is initially removed. The commercially available sodium hydroxide solution is continuously added to adjust the pH to 1-1.5 to precipitate the tin ions. The primary filtrate is obtained by filtering. Deionized water is added to the primary filtrate to a pH of 3-5 to remove copper and iron impurities. The secondary filtrate is obtained by filtering. The sodium hydroxide solution is continuously added to the secondary filtrate to adjust the pH to 5.5-7 to separate zinc and nickel to obtain ammonium nitrate solution. The current density is 100mA / cm 2 ; The catalyst is copper metal; the heavy metals in the nitric acid electroplating wastewater are mainly copper, tin, nickel and zinc;

[0049] S2. Preparation of nitrate ammonia fertilizer

[0050] The extracted ammonia is mixed with ammonium nitrate solution in a mass ratio of 1:1 to obtain a mixture, and then 9wt% of phosphorus and 6wt% of potassium are added to the mixture and mixed, and evaporated and concentrated under the conditions of 0.4MPa and 52°C to obtain liquid nitrogen fertilizer, and the liquid ammonia fertilizer is dried and granulated to obtain granular nitrate ammonia fertilizer with a particle size of 0.5-2mm; wherein, the drying method is natural drying, and the granulation adopts a commercially available dry roller granulator.

[0051] Example 2: Different from Example 1, the current density is 20 mA / cm 2 .

[0052] Example 3: Different from Example 1, the current density is 200 mA / cm 2 .

[0053] Embodiment 4: Different from Embodiment 1, carbon nanotubes are used as catalyst.

[0054] Embodiment 5: Different from Embodiment 1, the catalyst is copper-palladium alloy.

[0055] Embodiment 6: Different from Embodiment 1, the catalyst is a metal molecular complex.

[0056] Example 7: Different from Example 1, the extracted ammonia is mixed with ammonium nitrate solution in a mass ratio of 1:1 to obtain a mixture, and then 8wt% of phosphorus and 5wt% of potassium are added to the mixture respectively, and the mixture is evaporated and concentrated under the conditions of 0.3MPa and 45°C to obtain liquid nitrogen fertilizer, and the liquid ammonia fertilizer is dried and granulated to obtain granular nitrate ammonia fertilizer with a particle size of 0.5-2mm.

[0057] Example 8: Different from Example 1, the extracted ammonia is mixed with ammonium nitrate solution in a mass ratio of 1:2 to obtain a mixture, and then 10wt% of phosphorus and 7wt% of potassium are added to the mixture respectively, and the mixture is mixed and evaporated and concentrated under the conditions of 0.5MPa and 60°C to obtain liquid nitrogen fertilizer, and the liquid ammonia fertilizer is dried and granulated to obtain granular nitrate ammonia fertilizer with a particle size of 0.5-2mm.

[0058] Example 9: Different from Example 1, the catalyst is modified with a quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot material having an average particle size of 25 nm; the preparation method of the quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot material is:

[0059] 1) Under magnetic stirring, cadmium nitrate, chitosan and the first additive were mixed in a ratio of 1 mmol: 7 mmol: 1 mL, and a pH regulator was added to adjust the pH to 8 to obtain a cadmium precursor solution containing chitosan; nitric acid-containing wastewater, heavy metal precipitate and sulfur source were mixed and stirred in a ratio of 10 mL: 4 mmol: 7 mmol until all dissolved, and deionized water was added to dilute to S 2- The concentration of is 0.2mmol / L, and a sulfur precursor solution is obtained;

[0060] 2) then dripping the sulfur precursor solution into the cadmium precursor solution containing chitosan at a rate of 5 mL / s, adding the second additive at the same time, heating and reflux at a constant temperature of 92° C. for 3 to 5 hours, and collecting the first quantum dot solution;

[0061] 3) centrifuging the first quantum dot solution at a speed of 2800 r / min, removing the supernatant, and dispersing the resulting precipitate in n-octadecene at a concentration ratio of 7 mg / mL, repeating the operation three times, and finally dissolving the precipitate in deionized water to obtain a second quantum dot solution;

[0062] 4) nitrogen was passed through the second quantum dot solution at 26° C. for 25 min, and a quaternary ammonium salt solution and a nanosilver solution were sequentially injected with a syringe under magnetic stirring at a rate of 3 mL / min for 18 min, followed by heating under reflux at 93° C. for 6 h to obtain a reaction solution;

[0063] 5) The reaction solution was aged in a water bath at 105° C. for 1.2 h, crushed and granulated to obtain quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots;

[0064] The sulfur source is n-dodecyl mercaptan; the quaternary ammonium salt solution is composed of docosyl quaternary ammonium salt and deionized water in a weight ratio of 1:100; the nanosilver solution is composed of nanosilver and deionized water in a weight ratio of 1:23;

[0065] The first additive is a complexing agent, and the second additive is a surfactant; the complexing agent is ethylenediaminetetraacetic acid, and the surfactant is sodium dodecyl sulfate;

[0066] The modification method of the catalyst is as follows: first, the catalyst is ultrasonically dispersed in acetone with a concentration of 96% at a volume ratio of 30% to obtain a catalyst solution, and then the catalyst solution is ultrasonically mixed with quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots at a weight ratio of 6:7 to obtain a modified catalyst; the parameters of ultrasonic dispersion and ultrasonic mixing are: ultrasonic power of 150W, ultrasonic time of 32min, and ultrasonic temperature of 45°C.

[0067] Example 10: The difference from Example 9 is that 1) under magnetic stirring, 7 mol / mL cadmium nitrate solution, chitosan and the first additive are mixed in a ratio of 4 mL: 5 mmol: 1 mmol, and then a pH regulator is added to adjust the pH to 7 to obtain a cadmium precursor solution containing chitosan; nitric acid-containing wastewater, heavy metal precipitate and sulfur source are mixed and stirred in a ratio of 5 mL: 3 mmol: 5 mmol until all dissolved, and deionized water is added to dilute to S 2- The concentration is 0.15 mmol / L to obtain a sulfur precursor solution.

[0068] Example 11: The difference from Example 9 is that 1) under magnetic stirring, 7 mol / mL cadmium nitrate solution, chitosan and the first additive are mixed in a ratio of 10 mL: 10 mmol: 2 mmol, and then a pH regulator is added to adjust the pH to 9 to obtain a cadmium precursor solution containing chitosan; nitric acid-containing wastewater, heavy metal precipitate and sulfur source are mixed and stirred in a ratio of 15 mL: 5 mmol: 10 mmol until all dissolved, and deionized water is added to dilute to S 2- The concentration is 0.25 mmol / L to obtain a sulfur precursor solution.

[0069] Example 12: The difference from Example 9 is that 2) the sulfur precursor solution is then dripped into the cadmium precursor solution containing chitosan at a rate of 3 mL / s, and the second additive is added at the same time, and the mixture is heated to reflux at a constant temperature of 85° C. for 3 h, and the first quantum dot solution is collected.

[0070] Example 13: The difference from Example 9 is that 2) the sulfur precursor solution is then dripped into the cadmium precursor solution containing chitosan at a rate of 10 mL / s, and the second additive is added at the same time, and the mixture is heated to reflux at a constant temperature of 100° C. for 5 h, and the first quantum dot solution is collected.

[0071] Example 14: The difference from Example 9 is that 3) the first quantum dot solution is centrifuged at a speed of 2500 r / min, the supernatant is removed and the resulting precipitate is dispersed in n-octadecene at a concentration ratio of 5 mg / mL, the operation is repeated twice, and finally the precipitate is dissolved in deionized water to obtain a second quantum dot solution.

[0072] Example 15: The difference from Example 9 is that 3) the first quantum dot solution is centrifuged at a speed of 3000 r / min, the supernatant is removed and the resulting precipitate is dispersed in n-octadecene at a concentration ratio of 10 mg / mL, the operation is repeated 4 times, and finally the precipitate is dissolved in deionized water to obtain a second quantum dot solution.

[0073] Example 16: The difference from Example 9 is that 4) nitrogen gas is passed into the second quantum dot solution at 22°C for 15 min, and at the same time, under magnetic stirring, a quaternary ammonium salt solution and a nanosilver solution are injected in sequence with a syringe, the dripping rate is 1 mL / min, and the dripping time is 15 min, and then the solution is heated to reflux at 85°C for 3 h to obtain a reaction solution.

[0074] Example 17: The difference from Example 9 is that 4) nitrogen gas is passed into the second quantum dot solution at 30°C for 45 minutes, and at the same time, under magnetic stirring, a quaternary ammonium salt solution and a nanosilver solution are injected in sequence with a syringe, the dripping rate is 5 mL / min, the dripping time is 20 minutes, and then the mixture is heated to reflux at 100°C for 10 hours to obtain a reaction solution.

[0075] Example 18: The difference from Example 9 is that 5) the reaction solution is aged in a water bath at 30° C. for 0.5 h, and then crushed and granulated to obtain quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots.

[0076] Example 19: The difference from Example 9 is that 5) the reaction solution is aged in a water bath at 180° C. for 2 h, and then crushed and granulated to obtain quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots.

[0077] Example 20: Different from Example 9, the sulfur source is n-dodecyl mercaptan; the quaternary ammonium salt solution is composed of docosyl quaternary ammonium salt and deionized water in a weight ratio of 1:95; the nanosilver solution is composed of nanosilver and deionized water in a weight ratio of 1:20-25; the complexing agent is ethylenediaminetetraacetic acid, and the surfactant is sodium dodecyl sulfate.

[0078] Example 21: Different from Example 9, the sulfur source is sulfur powder; the quaternary ammonium salt solution consists of docosyl quaternary ammonium salt and deionized water in a weight ratio of 1:105; the nanosilver solution consists of nanosilver and deionized water in a weight ratio of 1:25; the complexing agent is polyacrylic acid, and the surfactant is sodium stearate.

[0079] Example 22: Different from Example 9, the catalyst modification method is as follows: first, the catalyst is ultrasonically dispersed in 95% acetone at a volume ratio of 20% to obtain a catalyst solution, and then the catalyst solution and quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots are ultrasonically mixed at a weight ratio of 3:5 to obtain a modified catalyst; the parameters of ultrasonic dispersion and ultrasonic mixing are: ultrasonic power of 100 W, ultrasonic time of 25 min, and ultrasonic temperature of 35°C.

[0080] Example 23: Different from Example 9, the catalyst modification method is as follows: first, the catalyst is ultrasonically dispersed in 97% acetone at a volume ratio of 40% to obtain a catalyst solution, and then the catalyst solution and quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dots are ultrasonically mixed at a weight ratio of 10:8 to obtain a modified catalyst; the parameters of ultrasonic dispersion and ultrasonic mixing are: ultrasonic power of 200 W, ultrasonic time of 40 min, and ultrasonic temperature of 50°C.

[0081] Embodiment 24: Different from Embodiment 9, the granular nitrate ammonia fertilizer is subjected to an enhanced treatment, and the enhanced treatment method is:

[0082] 1) A strongly acidic cation exchange resin containing carboxyl groups, a strongly basic anion exchange resin containing γ-polyglutamic acid and polylactic acid are mixed in a solvent in a ratio of 1:1:0.7:3, and ultrasonically dispersed at an ultrasonic intensity of 65W and an ultrasonic temperature of 28°C to obtain a mixed solution A; the content of carboxyl groups in the strongly acidic cation exchange resin containing carboxyl groups is 25wt%, the content of γ-polyglutamic acid in the strongly basic anion exchange resin containing γ-polyglutamic acid is 17wt%, and the solvent is dimethyl sulfoxide or water; wherein the strongly acidic cation exchange resin and the strongly basic anion exchange resin can be selected from any commercially available exchange resins, and in this embodiment, the strongly acidic cation exchange resin is D001 macroporous strongly acidic cation exchange resin; and the strongly basic anion exchange resin is D201 macroporous strongly basic styrene anion exchange resin;

[0083] 2) The mixed solution A is uniformly attached to the surface of the granular nitric ammonium fertilizer to obtain a strengthening film, which is then dried and solidified at 50° C. The thickness of the strengthening film is 25 nm, and the strengthening film is attached by vacuum magnetron sputtering or ion plating;

[0084] 3) Repeat step 2) 4 times to obtain granular nitrate ammonium fertilizer with a reinforced coating attached to the surface.

[0085] Example 25: The difference from Example 24 is that 1) a strongly acidic cation exchange resin containing carboxyl groups, a strongly basic anion exchange resin containing γ-polyglutamic acid and polylactic acid are mixed in a solvent in a ratio of 1:1:0.5:2, and ultrasonically dispersed at an ultrasonic intensity of 55 W and an ultrasonic temperature of 25°C to obtain a mixed solution A.

[0086] Example 26: The difference from Example 24 is that 1) a strongly acidic cation exchange resin containing carboxyl groups, a strongly basic anion exchange resin containing γ-polyglutamic acid and polylactic acid are mixed in a solvent in a ratio of 1:1:0.8:4, and ultrasonically dispersed evenly at an ultrasonic intensity of 75 W and an ultrasonic temperature of 30°C to obtain a mixed solution A.

[0087] Example 27: The difference from Example 24 is that the content of carboxyl groups in the strongly acidic cation exchange resin containing carboxyl groups is 20wt%, the content of γ-polyglutamic acid in the strongly basic anion exchange resin containing γ-polyglutamic acid is 15wt%, and the solvent is dimethyl sulfoxide.

[0088] Example 28: The difference from Example 24 is that the content of carboxyl groups in the strongly acidic cation exchange resin containing carboxyl groups is 30wt%, the content of γ-polyglutamic acid in the strongly basic anion exchange resin containing γ-polyglutamic acid is 18wt%, and the solvent is water.

[0089] Example 29: The difference from Example 24 is that 2) the mixed solution A is uniformly attached to the surface of the granular nitrate ammonium fertilizer to obtain a strengthened film, which is then dried and solidified at 40°C; the thickness of the strengthened film is 10 nm.

[0090] Example 30: The difference from Example 24 is that 2) the mixed solution A is uniformly attached to the surface of the granular nitrate ammonium fertilizer to obtain a strengthened film, which is then dried and solidified at 60°C; the thickness of the strengthened film is 50nm.

[0091] Experimental Example: The description of this experimental example is based on the schemes described in Examples 1 to 30, and is intended to illustrate the practical application effects of the present invention. The conversion rates of nitrate ammonia fertilizers obtained in Examples 1 to 30 and Control Groups 1 to 7 and the performance of nitrate ammonia fertilizers were tested respectively;

[0092] Conversion rate of nitrate ammonia fertilizer: Weigh about 10.00 g of each sample of Example 1 to Example 30, put them into a small bag made of 100 mesh nylon gauze, seal the small bag, put it into a 300 ml plastic bottle, add 250 ml of distilled water, cover and seal, and place them in a 25°C biochemical constant temperature incubator. Take samples on the 7th day, turn the bottle upside down 3 times (to make the concentration of the liquid in the bottle consistent) and move the sample into another small bottle, and calculate the conversion rate of nitrate ion to ammonia by conventional methods.

[0093] Performance of nitrate ammonia fertilizer: The fertilizers of Examples 1 to 30 and Control Groups 1 to 7 were all applied at one time, evenly spread on the surface of spring wheat in the wheat field, and the soil was deep-turned about 20 cm, sowed mechanically, and the yield increase rate was calculated after emergence; yield increase rate = (average yield after applying fertilizer (kg / mu) - average yield without applying fertilizer (kg / mu)) / average yield without applying fertilizer (kg / mu) × 100%. The conventional management of the wheat field was consistent with the conventional.

[0094] 1. Explore the impact of the steps of preparing nitrate ammonia fertilizer using nitric acid-containing electroplating wastewater on the ammonia conversion rate

[0095] Control group 1: Different from Example 1, the current density is 300 mA / cm 2 .

[0096] Conclusion: Figure 1 By comparing Examples 1 to 8 and Control Group 1, it can be seen that the current density, the selection of catalyst, and the ratio of ammonia to ammonium nitrate solution in the process of preparing nitrate ammonia fertilizer have little effect on the conversion rate of ammonia within the scope of the present application, and each parameter can achieve the best ammonia conversion effect under the conditions of Example 1. In Control Group 1, excessive current density will cause excessive heat to be generated during the electrolysis process, thereby reducing the electrolysis efficiency and also causing a decrease in the quality of the electrolysis product.

[0097] 2. Investigate the effect of ammonium salt / nanosilver modified chitosan-CdS quantum dots modification on ammonia conversion

[0098] Control group 2: Different from Example 9, chitosan was not added to the cadmium precursor solution.

[0099] Control group 3: Different from Example 9, no heavy metal precipitate was added to the sulfur precursor solution.

[0100] Control group 4: Different from Example 9, in step 3), n-octadecene was replaced by acetone.

[0101] Control group 5: Different from Example 9, in step 4), the step of injecting the quaternary ammonium salt solution and the nanosilver solution is missing.

[0102] Conclusion: Figure 2 From the comparison of Example 1 and Example 9 to Example 23, it can be seen that the modification of the catalyst with quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dots can effectively improve the conversion rate of ammonia. The main reason is that the quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot catalyst can attract nitrate ions by electrostatic action and inhibit the occurrence of other side reactions, so that nitrate is more likely to be converted into ammonia, thereby improving the ammonia conversion rate and further improving the preparation effect of nitrate ammonia fertilizer; and from the comparison of Example 9 to Example 23, it can be seen that the parameter change in the quantum dot modification process has little effect on the conversion rate of ammonia, and the best can be achieved under the conditions of Example 9; from Examples 9 to Example 11 and Control Groups 2 to Control Group 3 By comparison, it can be seen that not adding chitosan to the cadmium precursor solution or not adding heavy metal precipitates to the sulfur precursor solution will also cause a decrease in the conversion rate of ammonia. This is because chitosan can form a stable complex with metal nanoparticles. This complex can improve the catalytic activity of copper nanoparticles, allowing them to participate in the reaction more effectively during the electrolysis process, thereby improving the electrolysis efficiency, and then optimizing the conversion effect of ammonia and improving the preparation efficiency of nitrate ammonia fertilizer; the metal ions in the heavy metal precipitates will also be doped into the structure of the carbon nanotubes, and the sulfur element will also interact with the catalyst surface. This modification can adjust the electronic structure of the catalyst and improve its conductivity, thereby increasing the rate of the electrolysis reaction, improving the conversion rate of ammonia and further improving the preparation efficiency of nitrate ammonia fertilizer.

[0103] From the comparison of Example 9, Example 14 to Example 15 and Control Group 4, it can be seen that the use of acetone to disperse the first quantum dots will also cause a decrease in the conversion rate of ammonia. This is because compared with acetone, n-octadecene can make the quantum dots more evenly dispersed and reduce the agglomeration of quantum dots. When the quantum dots are used to modify the catalyst, the evenly dispersed quantum dots can interact with the catalyst surface more effectively, promote the reaction of nitrate conversion to ammonia, and reduce the side reactions that may cause nitrite generation, thereby increasing the ammonia conversion rate and reducing the nitrite content. At the same time, the stability of n-octadecene helps to maintain the structural integrity of the quantum dots, so that the quantum dots can play a better role when they are subsequently used to improve the performance of the catalyst, thereby indirectly increasing the ammonia conversion rate and reducing the content of by-product nitrite.

[0104] From the comparison of Example 9, Example 16 to Example 17 and Control Group 5, it can be seen that not performing quaternary ammonium salt / nanosilver modification will cause a decrease in the conversion rate of ammonia. This is because the catalyst modified with quaternary ammonium salt can attract nitrate ions by electrostatic action and inhibit the occurrence of other side reactions, making nitrate more inclined to be converted into ammonia, thereby improving the ammonia conversion rate, and also has good antibacterial properties, which can effectively inhibit the growth of bacteria in wastewater and reduce the interference of bacteria on the electrocatalytic process, thereby improving the recovery rate of ammonia; the high catalytic activity of nanosilver and the synergistic effect of chitosan-CdS quantum dots can accelerate the reduction reaction of nitrate ions; nanosilver can also form chemical bonds or physical adsorption with chitosan-CdS quantum dots to prevent the agglomeration and degradation of quantum dots, thereby maintaining the activity of the catalyst and extending its service life. It can be obtained that Example 9 has a better ability in improving the efficiency of nitrate ammonia fertilizer.

[0105] 3. Explore the impact of enhanced treatment on ammonia conversion rate and production performance

[0106] Blank group: Different from Example 24, no fertilizer was applied.

[0107] Control group 6: Different from Example 24, the strongly acidic cation exchange resin does not contain a carboxyl group.

[0108] Control group 7: Different from Example 24, the strongly basic anion exchange resin does not contain γ-polyglutamic acid.

[0109] Conclusion: Figure 3-4From the comparison of Examples 24 to 30, it can be seen that the enhanced treatment has no obvious effect on the ammonia conversion rate, but has a positive effect on improving the yield increase of nitrate ammonia fertilizer. This is because the granular nitrate ammonia fertilizer that has undergone enhanced treatment can limit the entry of water into the fertilizer to dissolve nitrate ammonia when the soil moisture is low, thereby enhancing the resistance to a humid environment; and when the ion concentration near the plant root system changes, it can release nitrate ammonia as needed to achieve the function of the fertilizer, thereby improving the yield increase rate of spring wheat; the control group 6 does not contain carboxyl groups, and the control group 7 does not contain γ-polyglutamic acid, which will cause the yield increase effect of nitrate ammonia fertilizer to weaken. This is because the arginine (containing amino groups) secreted by the plant roots, when close to the ions grafted with carboxyl groups, When exchanging the nitrate ammonia fertilizer coated with the resin, an acid-base neutralization reaction will occur between the carboxyl group and the amino group of arginine. When the ion concentration changes, especially when the plant roots absorb nitrate ammonia ions and cause the surrounding ion concentration to decrease, this coating change caused by the specific reaction can cause more nitrate ammonia ions to be released from the fertilizer; and because γ-polyglutamic acid has a strong water absorption, it can form a hydration layer on the surface of the ion exchange resin. When the soil moisture is low, this hydration layer can store a certain amount of water. The stored water will not be easily lost, thereby reducing the chance of water entering the fertilizer to dissolve nitrate ammonia, thereby achieving the targeted increase in production of nitrate ammonia fertilizer and improving its effect. In summary, the present application provides a new way to maximize the conversion of nitric acid electroplating wastewater into ammonia and then prepare it into nitrate ammonia fertilizer, thereby achieving the purpose of increasing resource utilization.

Claims

1. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid, characterized in that: The following steps are involved: S1. Electrocatalytic nitric acid-containing electroplating wastewater The nitric acid-containing electroplating wastewater is used as an electrolyte and passed through the cathode reduction zone into an electrochemical reactor. A catalyst is added according to a ratio of 1L of nitric acid-containing electroplating wastewater to a catalyst of 0.2-0.5g, and electricity is applied. The current is adjusted until nitrate ions in the electrolyte are reduced to obtain ammonia and collected. As the pH near the cathode increases, heavy metal precipitates are initially removed. The pH is further adjusted to 1-7 to remove the heavy metal precipitates for a second time, and the heavy metal precipitates are filtered to obtain an ammonium nitrate solution. S2. Preparation of nitrate ammonia fertilizer The extracted ammonia is mixed with an ammonium nitrate solution in a mass ratio of 1:1-2 to obtain a mixture, and then 8-10wt% of phosphorus and 5-7wt% of potassium are added to the mixture and mixed, and evaporated and concentrated under the conditions of 0.3-0.5MPa and 45-60°C to obtain liquid nitrogen fertilizer, and then the liquid ammonia fertilizer is dried and granulated to obtain granular nitrate ammonia fertilizer with a particle size of 0.5-2mm.

2. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid as claimed in claim 1, characterized in that: The current density is 20-200 mA / cm 2 .

3. The method for preparing nitrate ammonia fertilizer by utilizing electroplating wastewater containing nitric acid as claimed in claim 1, characterized in that: The catalyst is selected from any one of metallic copper, carbon nanotubes, copper-palladium alloy, and metal molecular complexes.

4. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid as claimed in claim 3, characterized in that: The catalyst is modified by a quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot material having an average particle size of 5 to 50 nm; the preparation method of the quaternary ammonium salt / nanosilver-modified chitosan-CdS quantum dot material is as follows: 1) Under magnetic stirring, 7 mol / mL cadmium nitrate solution, chitosan and the first additive are mixed in the ratio of 4-10 mL: 5-10 mmol: 1-2 mmol, and then a pH regulator is added to adjust the pH to 7-9 to obtain a cadmium precursor solution containing chitosan; nitric acid-containing wastewater, heavy metal precipitate and sulfur source are mixed and stirred in the ratio of 5-15 mL: 3-5 mmol: 5-10 mmol until all dissolved, and deionized water is added to dilute to S 2- The concentration of is 0.15-0.25 mmol / L, and a sulfur precursor solution is obtained; 2) then dripping the sulfur precursor solution into the cadmium precursor solution containing chitosan at a rate of 3 to 10 mL / s, adding the second additive at the same time, heating and reflux at a constant temperature of 85 to 100° C. for 3 to 5 hours, and collecting the first quantum dot solution; 3) centrifuging the first quantum dot solution at a speed of 2500-3000 r / min, removing the supernatant, dispersing the resulting precipitate in n-octadecene at a concentration ratio of 5-10 mg / mL, repeating the operation 2-4 times, and finally dissolving the precipitate in deionized water to obtain a second quantum dot solution; 4) nitrogen is passed through the second quantum dot solution at a temperature of 22 to 30° C. for 15 to 45 minutes, and a quaternary ammonium salt solution and a nanosilver solution are sequentially injected with a syringe under magnetic stirring, with a dripping speed of 1 to 5 mL / min and a dripping time of 15 to 20 minutes, and then heated under reflux at 85 to 100° C. for 3 to 10 hours to obtain a reaction solution; 5) aging the reaction solution in a water bath at a temperature of 30 to 180° C. for 0.5 to 2 h, crushing and granulating to obtain a quaternary ammonium salt / nanosilver modified chitosan-CdS quantum dot material; The sulfur source is n-dodecyl mercaptan or sulfur powder; the quaternary ammonium salt solution is composed of docosyl quaternary ammonium salt and deionized water in a weight ratio of 1:95-105; and the nanosilver solution is composed of nanosilver and deionized water in a weight ratio of 1:20-25.

5. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid as claimed in claim 4, characterized in that: The first additive is a complexing agent, and the second additive is a surfactant; the complexing agent is ethylenediaminetetraacetic acid or polyacrylic acid, and the surfactant is sodium dodecyl sulfate or sodium stearate.

6. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid as claimed in claim 4, characterized in that: The catalyst modification method comprises the following steps: firstly dispersing the catalyst in acetone with a concentration of 95-97% by ultrasonic at a volume ratio of 20-40% to obtain a catalyst solution, and then ultrasonically mixing the catalyst solution with chitosan-CdS quantum dots modified with quaternary ammonium salt / nanosilver at a weight ratio of 3-10:5-8 to obtain a modified catalyst; the parameters of the ultrasonic dispersion and ultrasonic mixing are: ultrasonic power of 100-200W, ultrasonic time of 25-40min, and ultrasonic temperature of 35-50°C.

7. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid as claimed in claim 1, characterized in that: The granular nitrate ammonia fertilizer is subjected to an enhanced treatment, wherein the enhanced treatment method is: 1) a strongly acidic cation exchange resin containing carboxyl groups, a strongly basic anion exchange resin containing γ-polyglutamic acid and polylactic acid are mixed in a solvent in a ratio of 1:1:0.5-0.8:2-4, and ultrasonically dispersed at an ultrasonic intensity of 55-75W and an ultrasonic temperature of 25-30°C to obtain a mixed solution A; 2) The mixed solution A is uniformly attached to the surface of the granular nitrate ammonium fertilizer to obtain a reinforced film, and then dried and solidified at 40-60°C; 3) Repeat step 2) 3 to 5 times to obtain granular nitrate ammonium fertilizer with a reinforced coating attached to the surface.

8. A method for preparing nitrate ammonia fertilizer using electroplating wastewater containing nitric acid as claimed in claim 7, characterized in that: In step 2), the thickness of the strengthening film is 10-50 nm, and the strengthening film is attached by vacuum magnetron sputtering or ion plating.

9. The method for preparing nitrate ammonium fertilizer by utilizing electroplating wastewater containing nitric acid as claimed in claim 7, characterized in that: The carboxyl content of the strongly acidic cation exchange resin containing carboxyl is 20-30 wt %, the gamma-polyglutamic acid content of the strongly basic anion exchange resin containing gamma-polyglutamic acid is 15-18 wt %, and the solvent is dimethyl sulfoxide or water.